Assessment practices in undergraduate clinical medicine training: What do we do and how we can improve? - Hanneke Brits; Johan Bezuidenhout; Lynette J. van der Merwe; Gina Joubert (AOSIS, 2020)
Background: Assessment should form an integral part of curriculum design in higher education and should be robust enough to ensure clinical competence. Aim: This article reports on current assessment practices and makes recommendations to improve clinical assessment in the undergraduate medical programme at the University of the Free State. Methods: A descriptive cross-sectional study design was used. Qualitative and quantitative data were gathered by means of open- and closed-ended questions in a self-administered questionnaire, which was completed by teaching and learning coordinators in 13 disciplines. Results: All disciplines in the undergraduate medical programme are represented. They used different assessment methods to assess the competencies required of entry-level healthcare professionals. Workplace-based assessment was performed by 30.1% of disciplines, while multiple-choice questions (MCQs) (76.9%) and objective structured clinical examinations (OSCEs) (53.6%) were the main methods used during formative assessment. Not all assessors were well prepared for assessment, with 38.5% never having received any formal training on assessment. Few disciplines (15.4%) made use of post-assessment moderation as a standard practice, and few disciplines always gave feedback after assessments. Conclusion: The current assessment practices for clinical students in the undergraduate medical programme at the University of the Free State cover the spectrum that is necessary to assess all the different competencies required. Multiple-choice questions and OSCEs, which are valid and reliable assessment methods, are used frequently. Poor feedback and moderation practices should be addressed. More formative assessments, and less emphasis on summative assessment, should be considered. Workplace-based and continuous assessments may be good ways to assess clinical competence.